Satisfação de clientes: um estudo realizado com a empresa Restaurante Rei de Ouro - Rodigheri, Maria Eduarda (2024)
The objective of this study is to evaluate the level of customer satisfaction at Restaurante Rei de Ouro, located in the city of Água Santa, RS. The research was conducted in two stages: the first, qualitative in nature, involved 21 interviewees, and the second, quantitative, was carried out through an online questionnaire using Google Forms, with the participation of 71 respondents. The collected data were tabulated and analyzed to measure the degree of customer satisfaction Reading service, the quality of the products offered, and the restaurant's environment. From this analysis, it was possible to identify the areas where the company achieves the highest satisfaction, as well as the aspects that need improvement to maintain or enhance these levels.